(NgUSX(B-(NhRUSTALXNYJ (B:s (Nw KNIGE RASSKAZYWAETSQ OB ISTORII PROSLAWLENNOJ GUSEWSKOJ HRUSTALXNOJ FABRIKI (B/s - (NkAZAKOWA(B, (Nl@DMILA wASILXEWNAs ((NmOSKWA (B:s (NsOWETSKIJ HUDOVNIK(B,s, 1973)
Resume, p. 209-211
(NhUDOVNIKI ZAWODA(B, (NSTR(B. 199-201s
(NbIBLIOGRAFIQ(B, (NSTR(B. 202-204s
(NsPISOK ILL@STRACIJ(B, (NSTR(B. 205-208s
Keywords: (NdEKORATIWNO(B-(NPRIKLADNOE ISKUSSTWOs; (NsTEKLO DEKORATIWNOEs; (NgUSX(B-(NHRUSTALXNYJ ZAWODs